Pengembangan Bahan Ajar Tematik Berbasis Kontekstual - Suci Perwitasari; Wahjoedi Wahjoedi; Sa'dun Akbar (Pascasarjana Universitas Negeri Malang, 2018)
Teaching materials that support thematic learning are essential for teachers and students in the learning process. Teaching materials that are appropriate to the student's condition and the student's student context (contextual) environment provide a meaningful learning experience for students. Therefore, the purpose of this study is the development of contextual thematic materials that are valid, practical, and effective. The research and development model used is Borg & Gall. This model was chosen because the stages are systematic and appropriate for developing printed materials. Data were collected through questionnaires, obervation sheets, and tests. The results of data analysis show that the book developed valid, practical, and effective use in learning. Bahan ajar yang mendukung pembelajaran tematik sangat penting bagi guru dan siswa dalam proses pembelajaran. Bahan ajar yang sesuai dengan kondisi siswa dan keadaan lingkungan tempat tinggal siswa (kontekstual) memberikan pengalaman belajar yang bermakna bagi siswa. Oleh karena itu, tujuan penelitian ini adalah pengembangan bahan ajar tematik berbasis kontekstual yang yang valid, praktis, dan efektif. Model penelitian dan pengembangan yang digunakan adalah Borg & Gall. Model ini dipilih karena tahapannya sistematis dan sesuai untuk mengembangkan bahan ajar cetak. Data dikumpulkan melalui angket, lembar obervasi, dan tes. Hasil analisis data menunjukkan bahwa buku.